The Self-Concept of Adolescents in Balai Gadang Kelurahan Koto Tangah District, Padang City - Maharani Jupriadi, Putri (Lembaga Riset Mutiara Akbar, 2022)
This research is motivated by the phenomenon of the existance of adolescents having probles with cognitive self-concept and affective self-concept. The purpose of this study was to describe: 1) The development profile of adolescent cognitive self-concept, 2) The development profile of adolescent affective self-concept. This research is a quantitative descriptive. The population in this study was 82 adolescents in the Balai Gadang Village, Koto Tangah Padang District. The sampling technique was total sampling. The reaserch instrument was a questionnaire and the data were processed using a percentage formula. The result of this study reveal that in general the self-concept of adolescents in the Balai Gadang Village, Koto Tangah Padang District, is in the fairly good category. Judging from each indicator: 1) Adolescent cognitive self-concept is in a fairly good category, including aspects of knowledge and aspects of an image as self-image. 2) Adolescent affective self-concept is in a fairly good category, including adolescent affective selfconcept from the aspect of self-acceptance and self-esteem aspects. It can be recommended to parents to pay more attention to their children so that they can help children in shaping a more posititive self-concept both in terms of cognitive and affective, as well as providing information to parents in developing adolescent cognitive and affective self-concepts